Legal-lay discourse and procedural justice in family and county courts - Grieshofer, Tatiana (Cambridge elements. Elements in forensic linguistics, 2024)
Focusing on adversarial legal settings, this Element explores discursive practices in court proceedings which often involve unrepresented parties - private family proceedings and small claims cases. Such proceedings present the main caseload of county and family courts, but pose immense challenges when it comes to legal-lay communication. Drawing on court observations, alongside textual and interview data, the Element pursues three aims: (1) developing the methodological and theoretical framework for exploring discursive practices in legal settings; (2) establishing the link between legal-lay discourse and procedural justice; (3) presenting and contextualising linguistic phenomena as an inherent part of court research and practice. The Element illustrates how linguistic input can contribute to procedural changes and court reforms across different adversarial and non-adversarial legal settings. The exploration of discursive practices embedded in court processes and procedures consolidates and advances the existing court research conducted within the fields of socio-legal studies and forensic linguistics. This title is also available as Open Access on Cambridge Core.